STRATEGI PEMASARAN UMKM BERBASIS DIGITAL MARKETING DI DESA KALANGGUNUNG CIPEUCANG PANDEGLANG – BANTEN - Ummy Kalsum; Alan Setiyadi; Sendi Arifin; Bunga Faradila Sari (LPPM Universitas Bina Bangsa, 2022)
Market research is the main problem for MSMEs, ignorance of the scope and scope of the market causes MSMEs to not focus on targeting the market. Conventional marketing, lack of capital and low digital mastery result in low MSME income and cashflow. New breakthroughs are needed in the field of digital management and digital marketing, production operations with all online business dynamics that are handled by themselves. The problems raised in this Community Service are: (1) introducing market research tools to MSMEs to find out the size and extent of their scope; (2) product operational limitations. This activity uses a digital marketing model with the selling method through E-Commerce. Therefore, we help SMEs in Kalanggunung Village. Through social media management by planning account creation, product photos, product descriptions. Everything is done on social media. In addition, the creation of a media platform marketplace to increase sales from the MSME business